The lntracavitary epiploplasty in the treatment of liver calcified hydatid cyst - Matteucci, Pablo (Cirugía del Uruguay, 1985)
Author presents a series ol 12 patients operated of li• ver calcified hydatid cysts with evacuation and epiploplasty of residual hydalid cavity, having ali of !hem recovered well within a short postoperative pe• riod.